Knowledge and Practice of Periodontal health among the students of Higher Institute of Medical Professions in Benghazi-Libya - Mahfoud, Salma O.; Al Ghazal, Logien B.; Alkhafifi, Hajer; Ben Amer, Najiya; Jamal, Rehab (Scientific Journal of University of Benghazi, 2021)
Periodontal diseases are a group of chronic inflammatory diseases that may cause tooth loss. For the past four decades, it has been documented that periodontal disease has an association with several systemic health issues such as cardiovascular diseases and diabetes. Prevention of periodontal disease requires continuous education from health care professionals. A cross-sectional survey study was conducted on 500 students from the Higher Institute of Medical Professions in Benghazi-Libya (HIMPS) to assess their knowledge regarding periodontal disease and how the participants practice daily oral hygiene. A structured interview questionnaire was used in this survey. All participants were informed orally about the nature and purpose of the study. This study showed that only 30% of the students at the HIMPS knew about dental plaque. Also, about 31% of the students knew of the association between periodontal disease and systemic diseases. Sixty per cent of the students used toothbrushes twice daily but only 33% of them used interdental cleaning aids. More dental education and awareness is required for health care professionals in Libya.